The Crisis of American Labor Operation Dixie and the Defeat of the CIO - Griffith, Barbara (Temple University Press, 1988)
Operation Dixie-the attempt by the Congress of Industrial Organizations (CIO) to unionize the postwar South-was on the defensive almost as soon as it began in 1946. Although the South had a longstanding reputation for being particularly unreceptive to organized labor, the CIO decided that a Southern drive was necessary to consolidate the considerable gains unions had made during the war and to remove the South as a non-union haven for "runaway" Northern businesses. Through extensive archival research and interviews with participants in the struggle, Barbara Griffith presents the dramatic account of the failure of Operation Dixie, examines the factors that contributed to its defeat, and specifies the ominous consequences for organized labor in America. The Crisis of American Labor offers an overview of the entire effort in the twelve-state region from 1946 to 1953. Much of the story is told in the words of the people who were involved: the organizers who staffed the drive and the employees they hoped to convince. Griffith includes extensive extracts from correspondence between organizers and labor leaders in the North as well as interviews with retired Operation Dixie organizers and Southern workers. The excerpts from these interviews are both enlightening and poignant, as they show how important this defeat was to the evolution of the South, the political economy, and race relations.